FAKTOR – FAKTOR DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN - Hendra, Hendra; Yusuf, Maulana (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This study aims to examine and analyze empirically the effect of liquidity, profitability, asset structure, corporate activity, and non-debt tax shield againts capital structure.The objects studied were companies in the textile and garment sub-sector and listed on the Indonesia Stock Exchange during the period 2012 to 2020. The sample selection technique used purposive sampling so that there were 6 companies and 54 samples that matched the criteria as samples. Then the data were analyzed using descriptive statistic and panel regression with FEM model. The results of this study are non-debt tax shield has a positive effect and corporate activity has an negative effect on capital structure. This because a company can use other non-debt investment which is more profitable to increase the value of firm, and company with good activity can afford their needs with sales and other investment activity and not depends on debt. Meanwhile liquidity, profitability, and assets structure don’t have an effect to capital structure.